2020
DOI: 10.18592/tarbiyah.v9i1.3543
|View full text |Cite
|
Sign up to set email alerts
|

The Application of The Polya's Steps Reviewed from Problem-Solving Ability in Two-Variable Linear Equation System (SPLDV)

Abstract: The ability of students in this school is low in understanding the questions given by the teacher. As a result they find it difficult to know the steps on how to solve the problem. Efforts that can be done are implementing Polya's steps.Quasi-experimental research was conducted in this study with the Randomized Control Group Only Design. Students of class VIII at this school are used as population. The experimental class is class VIIIA and the control class is class VIIIB. Final test data in the form of essays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…The results of previous research conducted by Widiana et al (2018) concluded that the use of the Polya-type problem-solving learning model provides better results compared to conventional learning models so the use of the Polya-type problem-solving learning model has a positive influence on problem-solving ability. In addition, research conducted by Sepriyanti et al (2020) concluded that the ability of students who use Polya steps to solve math problems gives better results than students who do not use Polya steps.…”
Section: Introductionmentioning
confidence: 99%
“…The results of previous research conducted by Widiana et al (2018) concluded that the use of the Polya-type problem-solving learning model provides better results compared to conventional learning models so the use of the Polya-type problem-solving learning model has a positive influence on problem-solving ability. In addition, research conducted by Sepriyanti et al (2020) concluded that the ability of students who use Polya steps to solve math problems gives better results than students who do not use Polya steps.…”
Section: Introductionmentioning
confidence: 99%
“…Langkah polya dapat dijadikan alternatif siswa dalam melakukan suatu pemecahanan masalah. Menurut (Sepriyanti et al, 2020) penggunaan langkah Polya dapat membantu memudahkan siswa dalam pemecahan suatu permasalahan. Melalui implementasi keempat langkah Polya, siswa dituntun dalam memahami suatu masalah sampai menyimpulkan hasil pekerjaan.…”
unclassified